A method for the production of high value products from coupling pre-treatment and fast pyrolysis

CN118146811BActive Publication Date: 2026-10-23NORTH CHINA ELECTRIC POWER UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410175739.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2026-10-23
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

由于草酸分解生成大量水和甲酸,液体产物中残留的甲酸和大量水分,不仅会影响液体产物的稳定性,还会导致产物不利于保存和运输

Benefits of technology

[0017]本发明将废弃生物质与草酸混合接触进行低温慢速热解预处理,得到脱水糖1,4∶3,6-二脱水-α-D-吡喃葡萄糖和高比表面积活性炭。废弃生物质和草酸具有不同的热稳定性,将两者混合接触,由于废弃生物质内半纤维素组分和草酸的热稳定性较差,在低温低氧条件下进行慢速热解预处理,在该温度下生物质中纤维素组分和草酸发生酯化反应但不分解,只会得到富含草酸酯化纤维素中间体的固体产物。将固体产物研磨至粉末后,固体产物可以实现快速升温,在无氧高温下进行快速热解,参与过酯化反应的纤维素组分会大量分解形成1,4∶∶,6-二脱水-α-D-吡喃葡萄糖,从而得到富含1,4∶3,6-二脱水-α-D-吡喃葡萄糖的液体产物和高比表面积、具有丰富含氧官能团的活性炭。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118146811B_ABST
    Figure CN118146811B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing high-value products by coupling pretreatment and fast pyrolysis, comprising the following steps: mixing waste biomass and oxalic acid, heating to 190-250 DEG C at a heating rate of 1-5 DEG C / min, and carrying out pyrolysis pretreatment under low-temperature and low-oxygen conditions with an oxygen content of 5-20%, grinding the obtained solid product into powder, and then carrying out pyrolysis under medium-high temperature and oxygen-free conditions at 350-450 DEG C to obtain pyrolysis steam, and condensing the pyrolysis steam to obtain liquid products rich in 1,4:3,6-dianhydro-alpha-D-glucopyranose and activated carbon. The method can obtain liquid products rich in 1,4:3,6-dianhydro-alpha-D-glucopyranose (DGP) and activated carbon with a high specific surface area and rich in oxygen-containing functional groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waste biomass utilization, specifically relating to a method for preparing high-value products by coupling pretreatment and rapid pyrolysis. Background Technology

[0002] Biomass resources are a type of carbon-containing renewable resource. Rapid pyrolysis technology can directly convert solid biomass into liquid bio-oil and solid pyrolysis char. Bio-oil has an extremely complex composition, containing various high-value-added chemicals such as furan derivatives and dehydrated sugar derivatives, but their content is generally very low, making them difficult to separate and extract. Therefore, to directly obtain bio-oil rich in specific high-value-added chemicals, the biomass pyrolysis process needs to be targeted and controlled to selectively promote the generation of specific target chemicals and inhibit the generation of other liquid byproducts. Furthermore, pyrolysis char can be reactivated at high temperatures to prepare commercial activated carbon for high-value utilization.

[0003] Dehydrated sugars are important products of the pyrolysis of cellulose and hemicellulose components in biomass, including levoglucan, levoglucone, and 1,4:3,6-dide-α-D-glucopyranose. Due to their unique chiral structures, these dehydrated sugar products have great potential for application in chemical synthesis. Currently, these dehydrated sugar products are not yet produced on a large scale industrially due to difficulties in preparation and high prices. When a suitable acidic catalyst is introduced into the pyrolysis process, rapid pyrolysis of cellulose can yield bio-oils rich in dehydrated sugar derivatives. Commonly used catalysts include inorganic acids (such as phosphoric acid and sulfuric acid), solid superacids, composite metal oxides, and zeolite molecular sieves. Although the addition of these catalysts can significantly improve the rapid pyrolysis process of cellulose, these catalytic processes face problems such as difficult catalyst recovery, environmental pollution, and high prices, limiting their large-scale industrial application. Therefore, there is a need to develop a green, pollution-free, and inexpensive method for preparing dehydrated sugar derivatives.

[0004] Activated carbon has wide applications in petrochemicals, food processing, pharmaceuticals, and even aerospace, and has become an important functional material for national economic development and national defense. Biomass pyrolysis char is one of the raw materials for producing activated carbon. It co-produces activated carbon while preparing liquid products through pyrolysis, greatly improving the utilization rate of biomass and avoiding resource waste.

[0005] Chinese patent applications CN201910903471.6 and CN201910903461.2 disclose methods for preparing a dehydrated sugar mixture by co-pyrolysis of microcrystalline cellulose and oxalic acid, and a method for preparing furfural by co-pyrolysis of corn cob and oxalic acid, respectively. However, since oxalic acid decomposes into formic acid at low temperatures, the two inventions yield mixed liquid products of dehydrated sugar mixture, furfural, and formic acid, respectively, which require further separation to obtain a purer target product. The paper "A sustainable strategy for the production of 1,4∶3,6-dianhydro-α-D-glucopyranose through oxalic acid-assisted fast pyrolysis of cellulose" published in Volume 436, Issue 13 of the *Chemical Engineering Journal* discloses a method for preparing 1,4∶3,6-dianhydro-α-D-glucopyranose by co-pyrolysis of microcrystalline cellulose and oxalic acid. Because oxalic acid decomposes into large amounts of water and formic acid, the residual formic acid and high water content in the liquid product not only affect its stability but also make it unsuitable for storage and transportation. Therefore, there is an urgent need for a method to prepare 1,4:3,6-disodehydrated-α-D-glucopyranose with low water and formic acid content. Chinese patent application CN200910193381.9 discloses a method and apparatus for preparing bio-oil and chemicals through staged pyrolysis of biomass. Utilizing the different pyrolysis characteristics of cellulose, hemicellulose, and lignin in biomass, cellulose and hemicellulose are first treated at low temperatures. This yields liquid products rich in organic carboxylic acids and aldehydes, liquid products rich in phenolic substances, and high-grade fuel. The remaining solid product is then pyrolyzed to obtain bio-oil with low water and acid content, improving the stability of the liquid product and making it more suitable for subsequent storage and transportation. In addition, Chinese patent application CN201310204271.4 also pre-treated corn stalks at low temperature by pyrolysis, and then used the different thermal stability of different components such as fructose, cellulose and lignin in corn cobs to perform secondary pyrolysis on the solid product to obtain a liquid product rich in 4-vinylphenol. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing high-value products by coupling pretreatment and rapid pyrolysis. This method can obtain liquid products rich in 1,4:3,6-disodehydrate-α-D-pyranose (DGP) as well as activated carbon with high specific surface area and abundant oxygen-containing functional groups.

[0007] To achieve the above objectives, the present invention provides a method for preparing high-value products by coupling pretreatment and rapid pyrolysis, comprising: mixing waste biomass and oxalic acid, heating to 190-250°C at a heating rate of 1-5°C / min, performing pyrolysis pretreatment under low-temperature and low-oxygen conditions with an oxygen content of 5-20%, grinding the obtained solid product into powder, and then performing pyrolysis under medium-high temperature and oxygen-free conditions at 350-450°C to obtain pyrolysis steam, and condensing the pyrolysis steam to obtain a liquid product rich in 1,4∶∶,6-disodehydrate-α-D-pyranose and activated carbon.

[0008] In the method for preparing high-value products by coupled pretreatment and rapid pyrolysis described in this invention, the mass ratio of waste biomass to oxalic acid is 1:5 to 1:11.

[0009] The method for preparing high-value products by coupling pretreatment and rapid pyrolysis according to the present invention has a reaction time of 1 to 2 hours for pyrolysis pretreatment.

[0010] The method for preparing high-value products by coupled pretreatment and rapid pyrolysis described in this invention has a particle size of 20-200 μm for the ground powdered solid product and a reaction time of 5-10 min at 350-450 °C.

[0011] The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to the present invention involves condensing the pyrolysis steam at a cooling rate of greater than or equal to 100°C / s.

[0012] The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to the present invention includes waste biomass comprising one or more of waste cotton clothing, cotton textile processing waste, straw, wood chips, microcrystalline cellulose, α-cellulose, and starch.

[0013] The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to the present invention includes oxalic acid comprising one or more of anhydrous oxalic acid, oxalic acid dihydrate, and oxalic acid trihydrate.

[0014] The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to the present invention involves mixing an inert gas with oxygen to form a low-oxygen condition, wherein the inert gas is one or more of nitrogen, helium and argon.

[0015] The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to the present invention, wherein the oxygen-free condition is to remove oxygen from the reaction system using an inert gas, wherein the inert gas is one or more of nitrogen, helium and argon.

[0016] The beneficial effects of this invention are:

[0017] This invention involves a low-temperature, slow pyrolysis pretreatment of waste biomass with oxalic acid to obtain the dehydrated sugar 1,4:3,6-didehydro-α-D-pyranose and high-specific-surface-area activated carbon. Waste biomass and oxalic acid have different thermal stability. Due to the poor thermal stability of the hemicellulose component in the waste biomass and oxalic acid, slow pyrolysis pretreatment is performed under low-temperature, low-oxygen conditions. At this temperature, the cellulose component in the biomass and oxalic acid undergo esterification but do not decompose, yielding only a solid product rich in oxalate-esterified cellulose intermediates. After grinding the solid product into powder, it can be rapidly heated and pyrolyzed at high oxygen-free temperatures. The cellulose component that participated in the esterification reaction decomposes significantly to form 1,4:3,6-didehydro-α-D-pyranose, resulting in a liquid product rich in 1,4:3,6-didehydro-α-D-pyranose and activated carbon with high specific surface area and abundant oxygen-containing functional groups.

[0018] This invention utilizes the slow pyrolysis pretreatment of biomass with oxalic acid as its core technology to reduce the formic acid and water content in the liquid product, thereby significantly improving the preservation capacity of bio-oil containing 1,4:3,6-disodehydrate-α-D-pyranose. By mixing biomass with oxalic acid and carrying out slow pyrolysis under controlled temperature and atmosphere conditions, the generation of formic acid and water is successfully reduced, further improving the quality of the bio-oil. This achieves high-yield and high-selectivity preparation of 1,4:3,6-disodehydrate-α-D-pyranose and reduces the complexity of subsequent processing and separation processes, thus providing a more efficient, economical, and environmentally friendly solution for the biomass conversion industry. Attached Figure Description

[0019] Figure 1 The image shows the infrared spectrum of the activated carbon obtained in Example 1.

[0020] Figure 2 The chromatogram of the liquid product obtained in Example 1 was obtained by gas chromatography / mass spectrometry. Detailed Implementation

[0021] The present invention will now be described in detail through embodiments. It should be noted that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.

[0022] The liquid product yield is calculated in the following examples:

[0023] Liquid product yield = Mass of collected liquid product ÷ Mass of biomass;

[0024] Moisture content = Mass of water in the collected liquid ÷ Mass of biomass;

[0025] In the following examples, the content of 1,4:3,6-disodehydrated-α-D-glucopyranose was analyzed by gas chromatography / mass spectrometry, and quantification was performed using the external standard method. The actual yield and selectivity of the product were calculated as follows:

[0026] DGP yield = mass of DGP ÷ mass of biomass

[0027] DGP selectivity = mass of DGP ÷ mass of organic product

[0028] = Mass of DGP ÷ (Mass of liquid product - Mass of water)

[0029] Unless otherwise specified, all percentages of yield in the following examples are by mass.

[0030] Unless otherwise specified, the experimental methods described in the following examples are conventional methods.

[0031] Example 1

[0032] 10g of dried microcrystalline cellulose was used as raw material. First, the microcrystalline cellulose and oxalic acid dihydrate were mechanically mixed uniformly at a mass ratio of 1:9. The mixture was then pyrolyzed slowly at 220℃ under a nitrogen and oxygen atmosphere (oxygen content 5%) with a heating rate of 1℃ / s and a solid-phase residence time of 2 hours. The resulting solid product was ground into a powder of 20–80 μm. Then, under a nitrogen atmosphere (oxygen content 0%), the powder was rapidly pyrolyzed at 400℃ with a solid-phase residence time of 5 minutes. The pyrolysis gas was condensed at a cooling rate of 100℃ / s to obtain a liquid product with a yield of 43.4% and a moisture content of 48.5%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed that the yield of DGP was 11.6% and the selectivity was 51.5%. Finally, the solid product was determined to have a specific surface area of ​​289.65 cm². 3 / g of activated carbon.

[0033] Example 2

[0034] 10g of dried α-cellulose was used as raw material. First, α-cellulose and anhydrous oxalic acid were mechanically mixed uniformly at a mass ratio of 1:5. The mixture was then pyrolyzed slowly at 190℃ under a nitrogen and oxygen atmosphere (oxygen content 20%) with a solid-phase residence time of 2 hours. The resulting solid product was ground into a powder of 50–100 μm. Then, under a nitrogen atmosphere (oxygen content 0%), the product was rapidly pyrolyzed at 450℃ with a solid-phase residence time of 10 minutes. The pyrolysis gas was condensed at a cooling rate of 120℃ / s to obtain a liquid product with a yield of 47.5% and a moisture content of 50.1%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed a DGP yield of 11.0% and a selectivity of 48.2%. Finally, the solid product was determined to have a specific surface area of ​​208.07 cm². 3 / g of activated carbon.

[0035] Example 3

[0036] 10g of dried straw was used as raw material. First, the straw and oxalic acid dihydrate were mechanically mixed evenly at a mass ratio of 1:7. The mixture was then pyrolyzed slowly at 210℃ under an argon and oxygen atmosphere (oxygen content 10%) with a heating rate of 5℃ / s and a solid-phase residence time of 2 hours. The resulting solid product was ground into a powder of 100–200 μm. Then, under an argon atmosphere (oxygen content 0%), the powder was rapidly pyrolyzed at 350℃ with a solid-phase residence time of 10 minutes. The pyrolysis gas was condensed at a cooling rate of 150℃ / s to obtain a liquid product with a yield of 41.7% and a moisture content of 45.9%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed a DGP yield of 7.5% and a selectivity of 39.3%. Finally, the solid product was determined to have a specific surface area of ​​210.69 cm². 3 / g of activated carbon.

[0037] Example 4

[0038] 10g of dried waste cotton clothing was used as raw material. First, the waste cotton clothing and oxalic acid trihydrate were mechanically mixed evenly at a mass ratio of 1:11. The mixture was then slowly pyrolyzed at 250℃ under an argon and oxygen atmosphere (oxygen content 5%) with a heating rate of 5℃ / s and a solid-phase residence time of 1 hour. The resulting solid product was ground into a powder of 150–200 μm. Then, under an argon atmosphere (oxygen content 0%), it was rapidly pyrolyzed at 400℃ with a solid-phase residence time of 5 minutes. The pyrolysis gas was condensed at a cooling rate of 100℃ / s to obtain a liquid product with a yield of 46.6% and a moisture content of 40.8%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed a DGP yield of 7.5% and a selectivity of 30.1%. Finally, the solid product was determined to have a specific surface area of ​​256.88 cm². 3 / g of activated carbon.

[0039] Example 5

[0040] 10 g of dried cotton textile processing waste was used as raw material. First, the cotton textile processing waste and anhydrous oxalic acid were mechanically mixed evenly at a mass ratio of 1:9. The mixture was then pyrolyzed slowly at 220℃ under a helium and oxygen atmosphere (oxygen content 20%) with a heating rate of 5℃ / s and a solid-phase residence time of 2 h. The resulting solid product was ground into a powder of 100–150 μm. Then, under a helium atmosphere (oxygen content 0%), the powder was rapidly pyrolyzed at 450℃ with a solid-phase residence time of 5 minutes. The pyrolysis gas was condensed at a cooling rate of 120℃ / s to obtain a liquid product with a yield of 48.2% and a moisture content of 43.3%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Cartesian moisture titrator showed a DGP yield of 7.0% and a selectivity of 28.2%. Finally, the solid product was determined to have a specific surface area of ​​227.65 cm². 3 / g of activated carbon.

[0041] Example 6

[0042] 10g of dried sawdust was used as raw material. First, the sawdust and oxalic acid trihydrate were mechanically mixed evenly at a mass ratio of 1:9. The mixture was then pyrolyzed slowly at 220℃ under a helium and oxygen atmosphere (oxygen content 5%) with a heating rate of 5℃ / s and a solid-phase residence time of 2 hours. The resulting solid product was ground into a powder of 100–150 μm. Then, under a helium atmosphere (oxygen content 0%), the powder was rapidly pyrolyzed at 350℃ with a solid-phase residence time of 10 minutes. The pyrolysis gas was condensed at a cooling rate of 100℃ / s to obtain a liquid product with a yield of 45.7% and a moisture content of 40.1%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed a DGP yield of 7.1% and a selectivity of 29.8%. Finally, the solid product was determined to have a specific surface area of ​​257.68 cm². 3 / g of activated carbon.

[0043] Comparative Example 1

[0044] 10g of dried microcrystalline cellulose with a particle size of 20-80μm was used as raw material. First, the microcrystalline cellulose and oxalic acid dihydrate were mechanically mixed uniformly at a mass ratio of 1:9. Under a nitrogen atmosphere (oxygen content 0%), rapid pyrolysis was performed at 400℃ with a solid-phase residence time of 5 minutes. The pyrolysis gas was condensed at a cooling rate of 100℃ / s to obtain a liquid product with a yield of 344.9% and a moisture content of 309.1%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed that the yield of DGP was 13.6% and the selectivity was 5.9%. Finally, the solid product was determined to have a specific surface area of ​​250.89 cm². 3 / g of activated carbon.

[0045] Comparative Example 2

[0046] 10g of dried microcrystalline cellulose was used as raw material. Under a nitrogen and oxygen atmosphere (oxygen content 5%), it was first slowly pyrolyzed at 220℃ with a heating rate of 1℃ / s and a solid-phase residence time of 2h. The resulting solid product was ground into a powder of 20–80μm. Then, under a nitrogen atmosphere (oxygen content 0%), it was rapidly pyrolyzed at 400℃ with a solid-phase residence time of 5 minutes. The pyrolysis gas was condensed at a cooling rate of 100℃ / s to obtain a liquid product with a yield of 38.5% and a moisture content of 35.0%. The pyrolysis liquid product was analyzed by gas chromatography / mass spectrometry and a Karl Fischer moisture titrator. The results showed that the yield of DGP was 1.1% and the selectivity was 0.6%. Finally, the solid product was determined to have a specific surface area of ​​15.33 cm². 3 / g of activated carbon.

[0047] Comparative Example 3

[0048] 10g of dried waste cotton clothing was used as raw material. First, the waste cotton clothing and oxalic acid trihydrate were mechanically mixed evenly at a mass ratio of 1:11. The mixture was then slowly pyrolyzed at 250℃ under an argon atmosphere (0% oxygen content) with a heating rate of 5℃ / s and a solid-phase residence time of 1 hour. The resulting solid product was ground into a powder of 150–200 μm. Then, under an argon atmosphere (0% oxygen content), the powder was rapidly pyrolyzed at 400℃ with a solid-phase residence time of 5 minutes. The pyrolysis gas was condensed at a cooling rate of 100℃ / s to obtain a liquid product with a yield of 45.0% and a moisture content of 37.9%. Analysis of the pyrolysis liquid product using gas chromatography / mass spectrometry and a Karl Fischer moisture titrator showed a DGP yield of 2.1% and a selectivity of 10.1%. Finally, the solid product was determined to have a specific surface area of ​​208.56 cm². 3 / g of activated carbon.

[0049] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing high-value products by coupled pretreatment and rapid pyrolysis, characterized in that, include: Waste biomass and oxalic acid are mixed and heated to 190–250°C at a heating rate of 1–5°C / min. The mixture is then subjected to pyrolysis pretreatment under low-temperature and low-oxygen conditions with an oxygen content of 5–20%. The resulting solid product is ground into powder and then pyrolyzed under medium-high temperature and oxygen-free conditions of 350–450°C to obtain pyrolysis steam. The pyrolysis steam is then condensed to obtain a liquid product rich in 1,4:3,6-disodehydrate-α-D-pyranose and activated carbon.

2. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The mass ratio of the waste biomass to oxalic acid is 1:5 to 1:

11.

3. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The reaction time for pyrolysis pretreatment is 1 to 2 hours.

4. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The particle size of the ground powdered solid product is 20-200 μm, and the reaction time at 350-450℃ is 5-10 min.

5. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The pyrolysis steam is condensed at a cooling rate of 100°C / s or higher.

6. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The waste biomass includes one or more of the following: waste cotton clothing, cotton textile processing waste, straw, wood chips, microcrystalline cellulose, α-cellulose, and starch.

7. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The oxalic acid includes one or more of anhydrous oxalic acid, dihydrate oxalic acid, and trihydrate oxalic acid.

8. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, Low-oxygen conditions are formed by mixing an inert gas with oxygen, wherein the inert gas is one or more of nitrogen, helium, and argon.

9. The method for preparing high-value products by coupled pretreatment and rapid pyrolysis according to claim 1, characterized in that, The oxygen-free condition is achieved by using an inert gas to remove oxygen from the reaction system. The inert gas is one or more of nitrogen, helium, and argon.

Citation Information

Patent Citations

  • Method and device for preparing bio-oil and chemicals by pyrolyzing biomass in steps

    CN101691495B

  • Method for coproducing 5-hydroxymethyl furfural, 4-vinylphenol and bio-oil by multi-stage pyrolysis of corn stalk

    CN103265506B

  • Method for preparing furfural through co-pyrolysis

    CN110642814A

  • Method for preparing dehydrated sugar mixture through copyrolysis of microcrystalline cellulose and oxalic acid

    CN110643748A